Bangladesher manobadhikar bishoyok Europio sommelon : . European Human Rights Conference on Bangladesh extremism,intolerance and violence : (Ekattorer Ghatok Dalal Nirmul Committee, 2005)
'Report on Human Rights in Bangladesh conference, London, June 17, 2005'